Towards Developing Team Management Software for Online Freelancing Work Offices Using the Slack Collaboration Tool - B. Palad, Eddie Bouy; G. Capangpangan, Kirby; S. Correos, Mailyn Joy; M. Tabigue, Marjorie (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Computers changed the way we think, learn, communicate, and recently, including the way we work. According to statistics, a Tot of people are now engaging in what we now know as Online Freelance work, or what we commonly call as ’Online Jobs? Because of this trend, employers have difficulty in managing their human resources especially if such online employees have to work in a virtual team. Therefore, this study addresses the issue on team management that is faced by different online organizations and offices nowadays. The authors come up with a solution to the manual monitoring of work teams which demands additional manpower and often difficult, costly and time consuming thus contributing to this under researched area on virtual teams. An application was developed to monitor the working time of each employee with their respective tasks and projects with the use of chat commands in a particular messaging application called Slack. The authors achieved the solution by the used of evolutionary prototyping and gone through phases of analyzing, prototype developing and testing each feature before deploying it in actual online marketing agency.